Implicações para a Inovação das Orientações Portuguesas de Avaliação Fármaco-Terapêutica - João Costa; Luís Silva Miguel; Guilherme Vitorino; Leonor Beja da Costa; Hugo Pedrosa; Susana Maia Lopes; Sofia André; Maria do Carmo Fonseca; Eurico Catro Alves (Formifarma, LDA., 2024)
Introduction:  The  growth  of  innovation  in  health  technologies  continues  to  pose  new  challenges  for  pharmaceutical  companies  and  authorities.  It  requires  increasingly  complex  assessment  processes  and  greater  expertise.  Recently,  the  Portuguese  authorities  updated  the  Health  Technology  Assessment  framework  with  new  guidelines  for  the  evaluation  of  Added  Therapeutic  Value.  Purpose:  The  aim  is  to  provide  an  overview  of  the  recent  updates  and  discuss  the  implications  for  future  innovative  therapeutics.  Methodology:  This  review  compared  the  new  guidelines  with  earlier  versions  and  was  followed  by  a  Think  Tank  discussion  with  an  expert  panel.  Results:  The  new  guidelines  introduced  relevant  changes  regarding  the  population(s),  comparators,  outcomes,  meta-analysis,  indirect  comparisons,  research  and  data  sources  and  final  assessment  decision(s).  Discussion:  These  changes  are  likely  to  affect  assessments  in  Portugal  directly  and  indirectly  with  implications  for:  defining  the  population,  indication(s),  comparators,  and  outcomes  of  future  studies;  analyzing  when  evidence  is  limited  and  dealing  with  increasingly  complex  assessments.  Some  strategies  are  suggested  to  support  future  assessments.  Conclusion:  Balancing  speed  and  accuracy  in  health  technology  assessments  will  be  key  for  faster  access  to  innovative  medicines  for  patients.  These  recent  updates  should  result  in  timely  and  more  robust  assessments,  and  ultimately  pave  the  way  for  the  future  of  health  technologies.